THE IMPACT OF FLIPPED CLASSROOM ON ENHANCING PHARMACOLOGY EDUCATION AMONG 3RD-YEAR MBBS STUDENTS. : JPUMHS;2024:14:04,171-175 .http://doi.org/10.46536/jpumhs/2024/14.04.576 - Kashif Rasheed Shaikh1, Umair Ali Soomro2, Muhammad Atif Ata3, Palwasha Abbasi4, Shuja Anwar Kazi5, Samreen Ali6, Mehwish Jaweed7 , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: Flipped Classroom FC is a creative academic methodology that shifts traditional learning standards by having students engage with content outside the classroom, frequently through web-based sources, and afterward apply this information in dynamic, in class works out. While the viability of FC has been investigated in different disciplines, its part in improving pharmacology training in medical colleges remains generally understudied. OBJECTIVES: This study means to assess the adequacy of the flipped classroom model in upgrading pharmacological information, decisive reasoning, and clinical application among third-year MBBS students at Suleman Roshan Medical College Tando Adam. METHODS: A cohort of 90 third-year MBBS understudies took part in this review. Students were taught pharmacology through the flipped study hall approach for a semester, with pre-class web based learning modules followed by interactive in-class exercises. Pre-and post-assessment scores and surveys on students’ perceptions were utilized to assess the adequacy of the flipped homeroom. RESULTS: The study showed huge enhancements in pharmacology information, with a post-evaluation score increase from 68% to 85%. Students reported high satisfaction with the flipped classroom approach, with 75% of students agreeing that it upgraded how they might interpret pharmacology and 70% revealing increased engagement. CONCLUSION: Flipped classroom is an effective teaching strategy for pharmacology training in MBBS students. It upgrades student’s commitment, encourages dynamic learning, and further develops clinical critical thinking skills. This approach ought to be coordinated into the pharmacology educational plan to help further learning and utilization of pharmacological ideas.